Altered Mental Distress Among Employees From Different Occupational Groups and Industries During the COVID-19 Pandemic in Germany. Issue 10 (9th October 2022) - Casjens, Swaantje; Taeger, Dirk; Brüning, Thomas; Behrens, Thomas
Abstract : The Covid-19 pandemic increased mental distress of non-healthcare workers with increased occupational SARS-CoV-2 infection risk (e.g., education and social work professionals, public administrative staff, bank clerks). Important factors to protect mental health of all employees would be improving workplace safety, facilitating interactions with colleagues, and supporting employees reduce work-privacy conflicts. Abstract : Objective: Mental distress of employees from the financial, public transport, public service, and industrial sector was examined in a cross-sectional study during the second COVID-19 (coronavirus disease 2019) wave in Germany and retrospectively at its beginning. Methods: Mental distress in terms of anxiety and depression symptoms was assessed with the Patient Health Questionnaire-4. High and potential occupational SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) infection risk (OSIR) was defined based on job information from 1545 non–health care workers. Results: The risks for more severe mental distress symptoms increased threefold and twofold, respectively, among employees with high and potential OSIR compared with employees without OSIR. Mental distress severity differed by the extent of work-privacy conflicts, perceived job protection, interactions with colleagues, and overcommitment. Conclusions: Reducing COVID-19 exposure through workplace protective measures, strengthening interactions among colleagues, and supporting employees with work-privacy conflicts could help better protect employees' mental health.